Lessons learned from one decade of developing agent-based tools for traffic modeling, simulation, and control: how to make cities smarter - Bazzan, Ana L. C. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2012: Anais do VIII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2012.14431, 2012)
While there is no definitive agenda for making cities smarter in terms of mobility, intuition says that information is key. However, contrarily to a more technical view, information should not only be consumed by the users, but also produced by them. This is already happening (smart-phones, social networks) but is far from being exploited by technical systems related to transportation. In this paper I discuss some of the issues related to more human-centered transportation system. It is argued that users of this system are somehow influencing it with their increasing coupled behaviors. Thus, there is a real opportunity for changing the paradigm in order to take advantage of the collective intelligence.